2019
DOI: 10.1061/(asce)cf.1943-5509.0001279
|View full text |Cite
|
Sign up to set email alerts
|

Wind Turbine Tower Failure Modes under Seismic and Wind Loads

Abstract: The main objective of this paper is to study the structural response and the failure modes of a typical wind turbine tower under different strong ground motions and wind loading based on a detailed finite element model of the tower. The ground motions were selected to match the design response spectrum with different design characteristic periods (Tg) in order to explore the influence of the frequency content of the earthquake on the response. The wind loads were generated from tropical cyclone scenarios. Nonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…The damage pattern 1 is consequential to the stress concentration due to the thickness difference between the transition piece (60 mm) and the main tower (30 mm). This agrees with, where the change in thickness led to the formation of plastic hinge at the tower base of a 1.5MW onshore wind turbine, which could spread towards the top and cause failure under extreme earthquake intensities ( PGA = 2 to 3 g). Thus, the damage pattern 1 may be avoided in OWTs that are to experience the near‐field crustal records with weak vertical components, by controlling the thickness between the substructure and the main tower in the design phase.…”
Section: Resultssupporting
confidence: 88%
“…The damage pattern 1 is consequential to the stress concentration due to the thickness difference between the transition piece (60 mm) and the main tower (30 mm). This agrees with, where the change in thickness led to the formation of plastic hinge at the tower base of a 1.5MW onshore wind turbine, which could spread towards the top and cause failure under extreme earthquake intensities ( PGA = 2 to 3 g). Thus, the damage pattern 1 may be avoided in OWTs that are to experience the near‐field crustal records with weak vertical components, by controlling the thickness between the substructure and the main tower in the design phase.…”
Section: Resultssupporting
confidence: 88%
“…However, the local blades details, such as airfoil shape, twist angle, and material distribution, are not only challenging to find but are also numerically complicated and computationally expensive. As a result, it is a common practice to either assume these details [5][6][7]10] and/or use the lumped mass approach to represent the RNA in finite element models (FEM) of wind turbines [1,11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the design and optimisation of composite blades using complex FE shell or solid element models to evaluate their strength and modal response [12][13][14][15]. Such high-fidelity FE models are difficult to implement with reasonable computational efficiency in earthquake engineering problems, particularly when a large number of numerical analyses of the whole rotor-towerfoundation-system is needed under a representative set of earthquake records [1,7,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The structural design of such towers has attracted the attention of many researchers (i.e., references [11][12][13][14][15][16]). Prevailing failure modes that dictate the design and determine the required cross-sections are the buckling of the tubular shells [17][18][19], fatigue of the connections [20][21][22] and avoidance of resonance between the tower's fundamental frequencies and the rotor and blade-passing frequencies, denoted as 1P and 3P, respectively [10,23].…”
Section: Introductionmentioning
confidence: 99%